2011
DOI: 10.1111/j.1365-2966.2011.18823.x
|View full text |Cite
|
Sign up to set email alerts
|

COLD GASS, an IRAM legacy survey of molecular gas in massive galaxies - II. The non-universality of the molecular gas depletion time-scale

Abstract: We study the relation between molecular gas and star formation in a volume‐limited sample of 222 galaxies from the COLD GASS survey, with measurements of the CO(1–0) line from the IRAM 30‐m telescope. The galaxies are at redshifts 0.025 < z < 0.05 and have stellar masses in the range 10.0 < log M★/M⊙ < 11.5. The IRAM measurements are complemented by deep Arecibo H i observations and homogeneous Sloan Digital Sky Survey and GALEX photometry. A reference sample that includes both ultraviolet (UV) and far‐infrare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

76
387
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(470 citation statements)
references
References 76 publications
76
387
6
Order By: Relevance
“…Davé et al, 2010Davé et al, , 2011Lagos et al, 2011;Popping et al, 2012Popping et al, , 2013, as well as observationally confirmed Saintonge et al, 2013;Tacconi et al, 2013;Santini et al, 2013). This trend is additionally seen in low-redshift galaxies, though Saintonge et al (2011) suggest that the gas fractions of low-z galaxies are more closely correlated with stellar density than stellar mass. We see this quantitatively for high-z SMGs in Figure 46, where we plot the gas fraction for all SMGs with CO (J=1-0) detections (to minimize the relatively large uncertainty in CO excitation; c.f.…”
Section: Molecular Gas Fractionsmentioning
confidence: 51%
See 2 more Smart Citations
“…Davé et al, 2010Davé et al, , 2011Lagos et al, 2011;Popping et al, 2012Popping et al, , 2013, as well as observationally confirmed Saintonge et al, 2013;Tacconi et al, 2013;Santini et al, 2013). This trend is additionally seen in low-redshift galaxies, though Saintonge et al (2011) suggest that the gas fractions of low-z galaxies are more closely correlated with stellar density than stellar mass. We see this quantitatively for high-z SMGs in Figure 46, where we plot the gas fraction for all SMGs with CO (J=1-0) detections (to minimize the relatively large uncertainty in CO excitation; c.f.…”
Section: Molecular Gas Fractionsmentioning
confidence: 51%
“…The results from Bigiel et al (2008) and Leroy et al (2008) are denoted by the colored contours in Figure 44. Utilizing a sample of 222 galaxies, Saintonge et al (2011) found an increasing molecular depletion time scale (where the depletion time scale is the inverse of ) with galaxy mass, while a roughly constant atomic gas depletion time scale across their mass range of 10 < logM * /M < 11.5.…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports that the Kennicutt-Schmidt correlation varies with some properties of galaxies (e.g., Saintonge et al 2011Saintonge et al , 2012Meidt et al 2013;Davis et al 2014). In addition, a simple relation does not fit to the center of our Galaxy (e.g., Longmore et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Right panels: the star formation efficiency as a function of specific star formation rate. The dashed lines show the COLD GASS results based on a sample of galaxies with secure CO detections (see Table 1 of Saintonge et al 2011). The small dots in the upper two panels represent spaxels located in the bulges.…”
Section: Discussionmentioning
confidence: 99%